2019
DOI: 10.1161/atvbaha.119.312461
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Use and Cardiovascular Disease

Abstract: While the opioid epidemic has garnered significant attention, the use of methamphetamines is growing worldwide independent of wealth or region. Following overdose and accidents, the leading cause of death in methamphetamine users is cardiovascular disease, because of significant effects of methamphetamine on vasoconstriction, pulmonary hypertension, atherosclerotic plaque formation, cardiac arrhythmias, and cardiomyopathy. In this review, we examine the current literature on methamphetamine-induced changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
146
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(173 citation statements)
references
References 63 publications
4
146
0
1
Order By: Relevance
“…The long‐term health effects of MA use include cognitive impairments, anxiety, insomnia, and cardiovascular disease (Darke, Duflou, & Kaye, 2017; Huckans, Fuller, Chalker, Adams, & Loftis, 2015; Kevil et al., 2019; Prakash et al., 2017). Aside from the neurotoxic effects and overdose, cardiovascular disease is the leading cause of death for MA users (Darke et al., 2017; Kevil et al., 2019). Compulsive drug use and craving are hallmark behaviours of addiction that are attributed to maladaptive changes in plasticity of dopamine (DA) neurons (Kauer & Malenka, 2007; Koob & Bloom, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The long‐term health effects of MA use include cognitive impairments, anxiety, insomnia, and cardiovascular disease (Darke, Duflou, & Kaye, 2017; Huckans, Fuller, Chalker, Adams, & Loftis, 2015; Kevil et al., 2019; Prakash et al., 2017). Aside from the neurotoxic effects and overdose, cardiovascular disease is the leading cause of death for MA users (Darke et al., 2017; Kevil et al., 2019). Compulsive drug use and craving are hallmark behaviours of addiction that are attributed to maladaptive changes in plasticity of dopamine (DA) neurons (Kauer & Malenka, 2007; Koob & Bloom, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…ethamphetamine (METH) is a highly addictive amphetamine class psychostimulant drug whose illicit use is dramatically increasing in the United States 1,2 . It has been reported that~1.6 million Americans used METH in 2017, with 964,000 cases (up from 684,000 cases in 2016) of emergency room visits owing to METH abuse associated disorders [3][4][5] .…”
mentioning
confidence: 99%
“…METH is toxic to both neuronal and cardiovascular systems; cardiovascular disease is the second leading cause of death among METH abusers following accidental overdose 6,7 . METH abuse associated with cardiovascular toxicity includes hypertension, tachycardia, cardiac arrhythmia, acute coronary vasospasm, myocardial infarction, and cardiomyopathy 1,2,[6][7][8] . Clinical case studies of the hearts of human METH users have revealed severely reduced left ventricular (LV) ejection fraction, LV chamber dilatation, myocardial lesions, cardiac hypertrophy, fibrosis, and inflammation in relatively younger patients (≤50 years) with no other significant cardiac risk factors 6,[9][10][11] .…”
mentioning
confidence: 99%
“…A high proportion of participants across all professional groups selected substance abuse as a risk factor for CVD (overall 81% of the whole sample). Studies from the general population have shown recreational drugs such as methamphetamine and cocaine can provoke a multifactorial dysfunction of the cardiovascular system [42,43]. Prevalence of substance abuse is high in people with schizophrenia [44], whereby between 40 and 50% of people with schizophrenia may have a comorbid substance use disorder (SUD) [45].…”
Section: Discussionmentioning
confidence: 99%